Beyond Detection: A Framework for Transforming Accessibility Evaluations into Implementable Fixes - Paula Palomino; André Araújo; Alenilton Silva; Rafael Araújo; Diego Dermeval; Grace Lis Porto; Sofia Simanke; Thiago Cordeiro; Rodrigo Lisboa (Journal on Interactive Systems)
Ensuring accessibility in government-managed digital platforms is essential for inclusive public services. However, accessibility evaluations often fail to produce actionable outcomes, creating a gap between assessment and implementation. This study presents a structured accessibility framework designed to bridge that gap by converting evaluation findings into implementable fixes. The framework integrates automated and manual assessments, maps each identified barrier to a user-centered justification, and generates structured action points that clearly assign responsibilities to development and design teams. The framework was tested through a pilot application on PNLD Formação (a Brazilian government platform developed as part of the public policy ”Programa Nacional do Livro e do Material Didático” – PNLD, or National Textbook Program) and empirically validated on PNLD Avaliação (another governmental platform supporting the pedagogic evaluation phase of the same policy). Additionally, a user survey conducted during the validation phase revealed not only critical usability challenges on one of the platforms but also misconceptions about accessibility and disability among system users. These findings highlight the need for both technical remediation and cultural awareness initiatives. This study contributes a replicable methodology for integrating accessibility evaluation into digital governance, fostering long-term accessibility improvements in large-scale platforms.